The expression (-6 + i)² is equivalent to which of the following expressions?

A.) 35

B.) -12i

C.) -12 + i

D.) 35 - 12i

E.) 37 - 12i

A.) 35

B.) -12i

C.) -12 + i

D.) 35 - 12i

E.) 37 - 12i

(-6 + i)²

= (-6 + i)(-6 + i) {when squaring a binomial, multiply it by itself}

= 36 - 6i - 6i + i² {used the foil method}

= 36 - 12i -1 {combined like terms, also i² is equal to -1}

= 35 - 12i {combined like terms}

= (-6 + i)(-6 + i) {when squaring a binomial, multiply it by itself}

= 36 - 6i - 6i + i² {used the foil method}

= 36 - 12i -1 {combined like terms, also i² is equal to -1}

= 35 - 12i {combined like terms}

**D.) 35 - 12i****Ask Algebra House**